Bird-Headed Dwarf of Seckel - Harsha Vardhan B; Muthu M; Saraswathi K; Koteeswaran D (Wolters Kluwer Medknow Publications, 2007)
Seckel syndrome is an extremely rare inherited disorder characterized by growth delays prior to birth resulting in low birth weight. Growth delays continue after birth resulting in short stature (dwarfism). This syndrome is associated with an abnormally small head, varying degrees of mental retardation and unusual "beak like" protrusion of nose. Other facial features may include abnormally large eyes, a narrow face, malformed ears and an unusually small jaw. This syndrome has an autosomal recessive pattern of inheritance. A case of the Seckel syndrome is presented.